Currency intervention and the global portfolio balance effect: Japanese lessons - Petra Gerlach-Kristen; Robert N. McCauley; Kazuo Ueda (The Economic and Social Research Institute (ESRI), 2012)
This paper shows that the Japanese foreign exchange interventions in 2003/04 seem to have lowered long-term interest rates in a wide range of countries, including Japan. It seems that this decline was triggered by the investment of the intervention proceeds in US bonds and that a global portfolio balance effect spread the resulting decline in US yields to other bond markets, thus easing global monetary conditions.
Keywords: 330; intervention; portfolio balance effect; Japan; Wechselkurspolitik; Öffentliche Anleihe; USA; Zinsstruktur; Öffentliche Anleihe; Währungsspekulation; Japan